Some results of studies of reactogenic and antigenic properties of local vaccine and epizootic strains in laboratory animals. - Ulugmuradov A.D. (Genius Journals, 2021)
This article describes the harmlessness and antigenic properties of local strains of brucellosis used in the manufacture of diagnostic agents and vaccines against brucellosis, which are extremely dangerous for humans and animals, as well as in experiments conducted on laboratory animals.
Keywords: Infection; focus; diagnosticum; prevention